Sementes inesperadas de um jardim (des)encantado: a construção político-eclesial da identidade de Igreja local no Japão: um estudo a partir do conflito com o Caminho Neocatecumenal - Oliveira, Antonio Genivaldo Cordeiro de (2016)
The research shows the construction of a unique identity in contemporary Japanese Catholicism. Utilizing primary sources, the author demonstrates a change in the paradigm of understanding of Catholic mission, with a historic-sociological reconstruction of the Catholic Church transplantation from the XIX century and the necessary accommodations during the expansionism of the Greater Japanese Empire. He then points out the Japanese episcopacy's participation in the Vatican II Council and highlights their commitment to inculturation issues and the construction of a local Church identity. Finally, he describes the emblematic conflict between the Newcatechumenal Way and the local Episcopal Conference in the past decades. The locus of this study is theoretically in regards to the religious transplantations and cultural transference process and its efforts to achieve an autochthonous identity. On the one hand, by demonstrating the formation of a Japanese identity within Catholicism, the study challenges the general understanding that Christianity continues to be considered as a foreign religion in Japan; on the other hand, it confirms the tendency of the Japanese people in appropriating a religious tradition and innovating it